Model development of Rejang culture-cased Islamic religious education textbook to improve hard work character - Aziza Aryati; Riyanto Riyanto; Bambang Sahono; Wasidi Wasidi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
Using a combined approach and the Research and Development/R&D method, this study aims to provide Rejang culture-based PAI textbooks that can improve the character of hard work in junior high school students in the Lebong district, as well as to assess whether the textbook is appropriate and effective for increasing the character of hard work in high school students. The research findings are as follows: 1) The following steps are taken to create Rejang culture-based PAI textbooks: First, conduct a needs assessment at the research site. The needs analysis results are used as the basis for compiling a draft textbook, secondly validating the draft textbook that has been made, thirdly revising the textbook in accordance with input from validators consisting of material experts, education experts, linguists, and practitioners/teachers, fourthly conducting limited trials of books that have been revised, fifthly revising based on consideration of the results of limited field trials, and sixthly conducting tr 2) PAI textbooks based on Rejang Culture are appropriate for developing a work ethic. 3) Rejang Culture-based PAI textbooks are effective at developing students' work ethic. The implication of this research is that as the distance between students and learning materials closes, the use of local culture in textbooks creates an attraction for reading books, fostering enthusiasm for learning, making it easier to absorb, understand, and achieve learning goals faster. Furthermore, using textbooks that incorporate elements of local culture can help students improve their character.